(NmETODIKA RUSSKOGO QZYKA (B:s (Nu^EBNOE POSOBIE (B/s - (NbARINOWA(B, (NeLENA aNATOLXEWNAs; (NbOVENKOWA(B, (NlIDIQ fEDOROWNAs; (NlEBEDEW(B, (NwASILIJ iWANOWI^s; (NbARINOWA(B, (NeLENA aNATOLXEWNAs ((NmOSKWA (B:s (NpROSWE]ENIE(B,s, 1974)
(NsPISOK LIT(B. (NW KONCE GLAW(B.s
Keywords: (NrUSSKIJ QZYK (B- (NmETODIKA PREPODAWANIQs